2005
DOI: 10.2337/diacare.28.3.702
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Dependent Vasodilation and Incidence of Type 2 Diabetes in a Population of Healthy Postmenopausal Women

Abstract: OBJECTIVE -Both postmenopausal state and diabetes are associated with endothelial dysfunction and are well-known risk factors for atherosclerosis. However, the relationship of endothelium-dependent vasodilation and diabetes has never been prospectively evaluated. This study provided the opportunity to assess the association between endothelial vasodilation function and the incidence of diabetes in a cohort of apparently healthy postmenopausal women.RESEARCH DESIGN AND METHODS -We conducted a prospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 43 publications
5
47
1
1
Order By: Relevance
“…With respect to the ACE inhibitors and ARBs, an improvement in endothelium-dependent flow-mediated vasodilation has been observed (32,33). The enhancement of endothelial function has been related to improved cardiovascular prognosis (34,35). Similarly, a reduction in albuminuria, which is also linked to the integrity of the endothelium, results in improved cardiovascular and renal prognosis (36,37).…”
Section: Secondary Efficacy End Pointsmentioning
confidence: 91%
“…With respect to the ACE inhibitors and ARBs, an improvement in endothelium-dependent flow-mediated vasodilation has been observed (32,33). The enhancement of endothelial function has been related to improved cardiovascular prognosis (34,35). Similarly, a reduction in albuminuria, which is also linked to the integrity of the endothelium, results in improved cardiovascular and renal prognosis (36,37).…”
Section: Secondary Efficacy End Pointsmentioning
confidence: 91%
“…ED is a mostly recognized part of macrovascular and microvascular disease complications in diabetes (16). ED may also precede diabetes onset and may promote insulin resistance and glucose dysregulation leading to diabetes, but there is still controversy about the exact role of ED in patients with prediabetes and diabetes (17,18). ED and atherosclerosis play an important role in the pathogenesis of end organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment studies in humans show that antioxidant therapy with vitamin C significantly improves endothelial dysfunction associated with insulin resistance (39) and that NOSmediated endothelial dysfunction in skeletal muscle is associated with impaired nutritive flow redistribution and diminished insulin-mediated and insulinindependent glucose uptake (40,41). We and others have recently shown that biomarkers of endothelial dysfunction are precursors of incident diabetes independent of obesity, inflammation, and other diabetes risk factors (42)(43)(44). Elevated concentrations of myeloperoxidase, whose availability and function are limited by consuming NO, are also a potent correlate of endothelial dysfunction (45).…”
Section: Discussionmentioning
confidence: 99%